Budaya Organisasi di Balai Wilayah Sungai Sumatera V SNVT Pelaksanaan Jaringan Pemanfaatan Air Ws. IAKR Padang - Alrima Charnevi; Syahril Syahril; Irsyad Irsyad; Lusi Susanti (Universitas Negeri Padang, 2021)
The purpose of this research is knowing about the organizational culture in Balai Wilayah Sungai Sumatera V SNVT Pelaksanaan Jaringan Pemanfaatan Air Ws. IAKR Padang. The methods of this research is quantitative descriptive. Data collection using primary data obtained from questionnaires with measurement instruments using the Likert scale. The result of the questionnaires have been tested for validity and reliability. The population of this study were all employees of Balai Wilayah Sungai Sumatera V SNVT Pelaksanaan Jaringan Pemanfaatan Air Ws. IAKR Padang. The technique used is proportionate random sampling with a total sample is 38 employees. The result showed that the organizational culture at Balai Wilayah Sungai Sumatera V SNVT Pelaksanaan Jaringan Pemanfaatan Air Ws. IAKR Padang is already in the strong category because it gets an average score of 3.84.